The Development of LKPD (Student Worksheet) Assisted by PhET Simulation on Sound Wave Material - Cahyani, Astiti Nur; Simbolon, Merta; Algiranto (MultiTech Publisher, 2024)
The development of a Student Worksheet (LKPD) assisted by PhET Simulation was motivated by the lack of practical equipment in school laboratories. This research aims to develop a Student Worksheet (LKPD) assisted by PhET Simulation on the subject of Sound Waves for Grade XI of Senior High School/Madrasah Aliyah (SMA/MA). The type of research used in this study is Research and Development (R&D) with a 4D development model (Define, Design, Develop, and Disseminate). During the development stage, the draft LKPD was described in terms of its feasibility and practicality. The feasibility data of the developed LKPD was obtained from the validation results by four experts consisting of two subject matter experts and two media experts using a questionnaire instrument. The practicality data of the LKPD was obtained from the responses of students and teachers to the use of the LKPD using a questionnaire instrument. The research involved 15 students in a limited trial. The results of this study indicate that the average score for the material aspect was categorized as